Supply Response of Kenyan Coffee in the World Market - Njaramba, Stephen G. (Kenyatta University, 2014)
The drastic drop in Kenya coffee supply in the last twenty years has severely affected the country's export revenues as well as the livelihoods of two million small scale producers and over six million people who directly or indirectly depend on coffee. In spite of the central role which coffee has played in the county's development, Coffee production has shown a steady decline over the last two decades. Coffee production declined from an all time high of about 130,000 metric tons in 1987/88 to a low of about 42,000 metric tons in the 2010 coffee calendar year In this study the objective was to estimate the response of Kenyan coffee which is supplied at the world market Coffee is an important crop to Kenya since it is a source of foreign exchange. It is also the main agricultural enterprise in some of the districts in the country and the major source of income to these districts. Therefore the research project sought to come up with the supply function of Kenyan coffee to the international market. Coffee supply in Kenya has continued to decline despite policy reforms in the coffee sector. The principal of cointegration and Error Correction Model were used to establish the effect of various variables to the supply of coffee to the international market. Despite the popular belief that falling international prices paid for coffee is the course of decline of supply from Kenya, this study found out that the international prices did not have significant effect on the supply of coffee from Kenya to the international market. Rather the supply is affected by cost of inputs both in the short and long run, the cost of moving coffee from the farm to the market, weather and the policies employed by the government. All the other variables were found to be insignificant at 5 percent level.